Introduction to 3D game programming with DirectX 9.0 : a shader approach. - Luna, Frank D., ....- (Plano : Wordware, 2006)
Presents an introduction to programming interactive computer graphics, with an emphasis on game development, using real-time shaders with DirectX 9.0. It teaches the fundamentals of Direct3D and shader programming, after which the reader will be prepared to go on and learn more advanced techniques. The book is divided into three main parts. Part I explains the mathematical tools that will be used throughout this book. Part II shows how to implement elementary 3D techniques, such as defining 3D geometry, lighting, texturing, alpha blending, and stenciling by using shaders and the HLSL. Part III is largely about applying Direct3D to implement a variety of interesting techniques and special effects, such as working with meshes, character animation, terrain rendering, picking, particle systems, environment mapping, normal mapping, and rendering to textures.
Keywords: Driedimensionele beeldverwerking; Programmeren